Enantiomeric separation of tramadol and Its metabolites: method validation and application to environmental samples - Silva, Cátia (2017)
The accurate assessment of racemic pharmaceuticals requires enantioselective analytical methods. This study presents the development and validation of an enantioselective liquid chromatography with a fluorescence detection method for the concomitant quantification of the enantiomers of tramadol and their metabolites, N-desmethyltramadol and O-desmethyltramadol, in wastewater samples. Optimized conditions were achieved using a Lux Cellulose-4 column 150 × 4.6 mm, 3 μm isocratic elution, and 0.1% diethylamine in hexane and ethanol (96:4, v/v) at 0.7 mL min-1. The samples were extracted using 150 mg Oasis® mixed-mode cation exchange (MCX) cartridges. The method was validated using a synthetic effluent of a laboratory-scale aerobic granular sludge sequencing batch reactor. The method demonstrated to be selective, accurate, and linear (r2 > 0.99) over the range of 56 ng L-1 to 392 ng L-1. The detection and the quantification limits of each enantiomer were 8 ng L-1 and 28 ng L-1 for tramadol and N-desmethyltramadol, and 20 ng L-1 and 56 ng L-1 for O-desmethyltramadol. The feasibility of the method was demonstrated in a screening study in influent and effluent samples from a wastewater treatment plant. The results demonstrated the occurrence of tramadol enantiomers up to 325.1 ng L-1 and 357.9 ng L-1, in the effluent and influent samples, respectively. Both metabolites were detected in influents and effluents.